Implementing fieldwork based on blended learning using geo-inquiry approach: will it work during the covid-19 pandemic? - Oktavianto, Dwi Angga; Utaya, Sugeng; Sumarmi; Taryana, Didik (International research in geographical and environmental education, 2024)
Fieldwork is an important part of geography education in many countries. However, little fieldwork-related activities are being observed in Indonesia, specifically at the senior secondary level. In an effort to address this issue, investigators have developed a fieldwork-based blended learning model to be used in the country. This study involved 187 students from three high schools who followed the developed learning model. To measure the effectiveness of the developed model, a correlational analysis that examined the effect of location and session allocation on the test scores of students was used. Questionnaires were distributed to gain insight into the responses of students toward the learning system and qualitative methods were used to capture the learning experiences of these students while using the model. The obtained results show that the grades of the students were significantly affected by location rather than study sessions. Furthermore, students responded positively to the fieldwork-based blended learning model, although traditional classroom learning remained the most preferred option. Interestingly, it was found that students in Indonesia preferred to study with large groups of classmates over smaller groups. These findings confirmed the hypothesis that cultural and religious factors, specifically the concepts of "gotong royong" and "jama'ah" in Islam, respectively, influenced the perceptions of students and group preferences when studying.